Price Impact Asymmetry of Block Trades: An Institutional Trading Explanation - Saar, Gideon (Review of Financial Studies, 2001)
This article develops a theoretical model to explain the permanent price impact asymmetry between buyer- and seller-initiated block trades (the permanent price impact of buys is larger than that of sells). The model shows how the trading strategy of institutional portfolio managers creates a difference between the information content of buys and sells. The main implication of the model is that the history of price performance influences the asymmetry: the longer the run-up in a stock's price, the less the asymmetry. The intensity of institutional trading and the frequency of information events affect the asymmetry differently depending on recent price performance.